Synthesis and antitumor evaluation of neolaxiflorin B inspired compounds - Liu JP; Xiao YZ; Hu Y; Li XN; Wu MJ; Zhao Y; Zhao Y; Ma ZJ; Shen J (Dove Medical Press, 2019)
Jing-Ping Liu,1 Ye-Zhi Xiao,1 Yu Hu,1 Xiao-Nian Li,2 Ming-Jiang Wu,3 Yong Zhao,1 Yan Zhao,1 Ze-Jin Ma,1 Jing Shen11Department of Chemistry, Yunnan Normal University, Kunming 650092, People’s Republic of China; 2State Key Laboratory of Phytochemistry and Plant Resources in West China, Kunming Institute of Botany, Kunming 650201, People’s Republic of China; 3Criminal Science and Technology Key Lab of Yunnan Police College, Kunming 650223, People’s Republic of ChinaCorrespondence: Jing-Ping Liu; Jing ShenDepartment of Chemistry, Yunnan Normal University, No. 298, 121st Street, Yunnan, Kunming 650092, People’s Republic of ChinaTel/Fax +86 8 716 513 2144Email Liujp72@163.com shenjingbox0225@hotmail.comBackground: Neolaxiflorin B is derived from ent-kaurane like laxiflorin J and eriocalyxin B with a relatively low potency as an antitumor agent. During preliminary structure–activity relationship studies, the α,β-unsaturated ketone (enone) system is an important active group.Methods: Seven neolaxiflorin B derivatives containing α,β-unsaturated ketone moieties were synthesized. In vitro, activity was evaluated against three human tumor cell lines and a rat myogenic cell line (HepG2, NSCLC-H292, SNU-1040, and L6, respectively) by MTT assay.Results: Compound 15 appeared a promising antitumor lead due to its cytotoxic potency and relatively high selectivity, with an SI value of 13.14. Flow cytometry analysis was conducted to show that NSCLC-H292 cells were blocked in the G0/G1 phase in the presence of compound 15, thus inhibiting the proliferation of tumor cells.Conclusion: This study has revealed that compound 15 is a promising antitumor lead due to the cytotoxic potencies and the high selectivity it displayed when compared to natural counterparts.Keywords: neolaxiflorin B inspired compounds, unsaturated ketone, antitumor activity